Trends in investments in port infrastructure in the Mediterranean countries: convergence or divergence to EU policies? - Χλωμούδης, Κωνσταντίνος Ι.; Πάλλης, Αθανάσιος Α. (SPOUDAI Journal of Economics and Business, 2002)
As Mediterranean ports and the state of their infrastructure turn to critical parts of the European transportation networks, this paper analyses the trends in Investments in Port Infrastructure (IPI) in four Mediterranean EU member states: Portugal, Spain, Italy and Greece. To remain competitive, ports need to integrate to multimodal networks. The improvement of their infrastructure consists a decisive factor of this process. A selective modal allocation of the investments devoted in transport infrastructure can also advance the use of environmentally friendly transport modes through. As these demands have became EU policy targets, the paper focuses on the national IPI policies followed in the Mediterranean countries assessing whether they converge to EU policies. The findings suggest that, contrasting the policy targets that have been set in the Common Transport Policy (CTP), the level of the investments devoted to projects aiming to improve port infrastructure follows a negative trend in all the cases under examination. JEL Classification: L91, R41